Coupled dark energy: parameter constraints from N-body simulations - Macciò, Andrea V.; Amendola, Luca (Physical review. D, Particles, fields, gravitation, and cosmology, 2004)
We investigate cosmologies where dark matter (DM) is coupled to dark energy (DE), through N-body simulations. The dark-dark coupling introduces two novel effects in particle dynamics: (i) DM particle masses vary with time; (ii) gravity between DM particles is ruled by a constant G*, greater than Newton’s constant G, holding in other two-body interactions. Hence, DM particle dynamics violates the equivalence principle and, as a consequence, baryons and DM particle distributions develop a large scale bias. Here we focus on DE models with Ratra-Peebles (RP) potentials. The dark-dark coupling is set in a parametric range compatible with background and linear dynamics. We find that nonlinear dynamics puts additional constraints on the coupling parameter. They mostly arise from cluster density profiles that we find to yield higher concentrations in coupled RP models, with respect to (uncoupled) dynamical DE cosmologies. Such an enhancement, although being a strong effect in some coupling parameter range, leads to acceptable observables for a significant range of values of the coupling parameter. We also analyze the expected cluster mass function and the DM-baryon bias in nonlinear conditions, finding them compatible with data. With the above restrictions, coupled DE models with a RP potential are therefore consistent with cosmological nonlinear observables. As a general conclusion, we confirm that cosmologies with a suitable dark-dark coupling are viable theories.
Gesehen am 17.11.2017